Identification of Two bZIP Transcription Factors Interacting with the Promoter of Soybean Rubisco Activase Gene (GmRCAα) - Zhang, Jinyu; Du, Hongyang; Chao, Maoni; Yin, Zhitong; Yang, Hui; Li, Yakai; Huang, Fang; Yu, Deyue (Frontiers in Plant Science, 2016)
Rubisco activase (RCA), a key photosynthetic protein, catalyses the activation of Rubisco and thus plays an important role in photosynthesis. Although the RCA gene has been characterized in a variety of species, the molecular mechanism regulating its transcription remains unclear. Our previous studies on RCA gene expression in soybean suggested that expression of this gene is regulated by trans-acting factors. In the present study, we verified activity of the GmRCAα promoter in both soybean and Arabidopsis and used a yeast one-hybrid (Y1H) system for screening a leaf cDNA expression library to identify transcription factors (TFs) interacting with the GmRCAα promoter. Four basic leucine zipper (bZIP) TFs, GmbZIP04g, GmbZIP07g, GmbZIP1 and GmbZIP71, were isolated, and GmbZIP04g and GmbZIP07g were confirmed as able to bind to a 21-nt G-box-containing sequence. Additionally, the expression patterns of GmbZIP04g, GmbZIp07g and GmRCAα were analysed in response to abiotic stresses and during a 24-h period. Our study will help to advance elucidation of the network regulating GmRCAα transcription.